Not Ceded but Redistributed - Williams, Joe (Sovereignty & indigenous rights: the Treaty of Waitangi in international contexts, 1991)
Keywords: government relations; kāwanatanga; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; tāngata whenua

Te mana, te kāwanatanga: the politics of Māori self-determination - Durie, Mason (Oxford University Press, 1998)
Keywords: government relations; kāwanatanga; law; self-determination; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

He Whakaatanga o te ao: the reality - Ihimaera, Witi; Williams, Haare; Ramsden, Irihapeti; Long, D. S. (Te ao mārama : regaining Aotearoa : Māori writers speak out ; v. 2, 1993)
Keywords: ethnic identity; government; government relations; social conditions; te reo māori; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

Tino Rangatiratanga: Māori Self Determination - Durie, Mason (He Pukenga Kōrero: a journal of Māori studies, 1995)
Keywords: kotahitanga; mātauranga māori; social life and customs; tino rangatiratanga; tāngata whenua

Representation, Governance and the Goals of Māori Self Determination - Durie, Mason (He Pukenga Korero: a journal of Māori studies, 1997)
Keywords: māori electorates; mātauranga māori; parliament; representation; social life and customs; tino rangatiratanga; tāngata whenua

Māori Representation in Parliament and Tino Rangatiratanga - Dahlberg, Tina (He Pukenga Korero: a journal of Māori studies, 1996)
Keywords: government; māori electorates; mātauranga māori; parliament; social life and customs; tino rangatiratanga; tāngata whenua

The Role of Maori women in Treaty Negotiations and Settlements - Rangiheuea, Tania (1995)
Keywords: crown; māori decision making; tino rangatiratanga; treaty settlements; wāhine māori

Mana Maori Motuhake: Maori Self-Determination - Levine, Hal; Henare, Manuka (Pacific Viewpoint, 1994)
Keywords: elections; he whakaputanga; land loss; mana motuhake; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; urbanisation; waitangi tribunal

'Te Wai-Kaukau o nga matua tipuna': myths, realities, and the determination of mana whenua in the Waikaremoana district. - Wiri, Robert K. J. (ResearchSpace@Auckland, 1994)
In the heart of the North Island of New Zealand lies a mountainous terrain called Te Urewera, the spiritual homeland of the Tϋhoe people. Hidden away in the southern portion of Te Urewera is Waikaremoana, a lake and a land with a history and tradition that are as fascinating as they are controversial. Waikaremoana is the 'tūrangawaewae' of the Ngāti Ruapani section of Tūhoe, and it is they and their lands that are the key focus of this M.A thesis. This thesis deals essentially with the concept of land ownership or mana whenua. It analyses the relationship between customary and colonial concepts of mana whenua in the Waikaremoana district, and examines the conflicting nature of these two different cultural concepts of the land and its history. In many ways this dissertation is unique, as it is a tribal history written by tangata whenua for tangata whenua. It allows today's tangata whenua to see their history through their predecessor's eyes and reawakens the past struggles of their ancestors. It gives tangata whenua a sense of dignity and pride in their heritage and traditions that give them their identity. 'Ko te uri o Tūhoe, moumou kai, moumou tāonga, moumou tangata ki te pō!'
Keywords: iwi; mana whenua; tino rangatiratanga

The practice of tribalism in postcolonial New Zealand - Sullivan, Ann (Cultural Studies, 1995)
Keywords: post-colonialism; tikanga | indigenous law; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; urbanisation